Activated Carbon from Jackfruit Peel Waste ss Decolouring Agent of Screen Printing Waste Water - Sri Sunarsih; Sri Hastutiningrum; Tifani Diah Nisa (Seminar Nasional Teknik Kimia Kejuangan, 2016)
The aim of this research was to create decolouring agent of screen printing waste water by using activated carbon from jackfruit peel waste as an adsorbent. The carbonization process of jackfruit peel waste has been done in temperature 907o C in the absence of air and activated with sulfuric acid in different concentration (3, 5, 7, 9 and 11%). The adsorption capacity of activated carbon found out by interacting it with 25 mL of screen printing waste water. Furthermore, some test had been done to find out the influence of different particle size, weight of adsorbent and interaction time. The effect of different particle size was examined at 20, 40 and 60 mesh, the effect of the weight of adsorbent in 100, 125, 150, 175 and 200 mg and interaction time at 15, 30, 60, 90 and 120 minutes. Optimum capacity of activated carbon reached at 11% concentration of sulfuric acid, particle size 40 mesh, with the weight 200 mg and time interaction of 90 minutes